2003
DOI: 10.1007/s10047-003-0232-x
|View full text |Cite
|
Sign up to set email alerts
|

Intimal hyperplasia and hemodynamic factors in arterial bypass and arteriovenous grafts: a review

Abstract: Stenosis at the graft-vein junction caused by intimal hyperplasia (IH) is the major cause of failure of vascular access grafts used for hemodialysis. There is a strong relationship between hemodynamic factors and formation of IH. The hemodynamic pattern and the location of IH are different in arterial bypass grafts (ABGs) compared with arteriovenous grafts (AVGs). In an ABG, end-to-side anastomosis of the expanded polytetrafluoroethylene graft and artery produces hemodynamic changes around the junction. IH dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
237
0
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(251 citation statements)
references
References 68 publications
2
237
0
12
Order By: Relevance
“…In activated ECs, increased expression of growth factors at the gene and protein levels (such as HDAC3 and PDGF-2) promote SMC migration from the media to the intima as well as proliferation (10). Proliferation of SMCs in the intima is associated with deposition of extracellular matrix, a process analogous to scar formation (9,11). The overall result is the rapid formation of a neointimal layer over the site of injury.…”
Section: Mechanisms Of Intimal Hyperplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…In activated ECs, increased expression of growth factors at the gene and protein levels (such as HDAC3 and PDGF-2) promote SMC migration from the media to the intima as well as proliferation (10). Proliferation of SMCs in the intima is associated with deposition of extracellular matrix, a process analogous to scar formation (9,11). The overall result is the rapid formation of a neointimal layer over the site of injury.…”
Section: Mechanisms Of Intimal Hyperplasiamentioning
confidence: 99%
“…Thus, low WSS activates a cascade of molecular events that lead to leukocyte adhesion and migration into the intimal layer of the vasculature. Hemodynamically induced neointimal hyperplasia has been related not only to low WSS but also to stagnation points of the circulation (11). That low WSS is the major determinant of intimal thickness was demonstrated in vivo in dogs by Morinaga and colleagues in 1985 (34), who clearly showed that the change in WSS, but not the rate of blood flow, is the essential hemodynamic factor related to neointimal hyperplasia in autogenous vein grafts.…”
Section: Disturbed Flow As An Upstream Event In Neointimal Hyperplasiamentioning
confidence: 99%
“…Numerous studies have shown that synthetic TEBVs and autologous vein grafts exhibit compliance and caliber mismatch with their recipient arteries, which elicits intimal hyperplasia leading to graft apatency. [43][44][45] Therefore, achieving a close match of caliber and compliance between the graft and the recipient artery is of critical importance. Using the methods described here, TEBVs can be fabricated with diameters that match recipient vessels and with compliances within natural ranges.…”
Section: Figmentioning
confidence: 99%
“…It is believed that this plays a major role in postoperative complications and ultimate graft failure. [4][5][6] Thus, there is a need to create a biomaterial with properties tuned for specific cardiovascular device applications.…”
Section: Introductionmentioning
confidence: 99%